Multi-Circular SAR Three-Dimensional Image Formation via Group Sparsity in Adjacent Sub-Apertures - Weixing Yang; Daiyin Zhu (Remote Sensing, 2022)
Multi-circular SAR(MCSAR) can obtain holographic three-dimensional (3D) images of interesting observation targets, which is a significant research field at present. For anisotropic scatterers, the multi-circular SAR incoherent 3D imaging strategy combines the principle of tomography SAR inversion to obtain better reconstruction results. However, in incoherent 3D imaging, the traditional L1-norm regularization method only considers sparse representation and reconstruction in the sub-aperture pixel unit along the elevation direction, and the target structural sparsity in the same pixel unit between adjacent sub-apertures is not considered. The hierarchical sparsity constraint method in multi-circular SAR 3D target reconstruction is proposed in this paper, the L1-norm regularization is used in sub-aperture elevation, and the L2,1-regularization-based group sparsity constraint is adopted in elevation of the adjacent sub-aperture. In this paper, the sparse group thresholding iterative method is proposed to reconstruct the 3D observed target image with MCSAR data. Compared with the traditional L1-norm regularization method and IAA-GLRT method for MCSAR target reconstruction in elevation, the proposed method in this paper could obtain clearer 3D observation target images, with fewer desultory points along the elevation direction. Detailed simulation data analysis and 3D imaging processing of real MCSAR data demonstrate the advantages of the proposed method.